PENGEMBANGAN MEDIA EDUKATIF PADA PEMBELAJARAN SENI MUSIK MELALUI LAGU “MANUK DADALI” UNTUK MENINGKATKAN NASIONALISME SISWA KELAS IV SD SUNAN GIRI - Najwa May Maharani, Aqilah; Andika Gutama; Aqilah Najwa May Maharani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Music learning in elementary schools is still predominantly conducted through conventionalsinging activities without the support of interactive and concrete learning media, resulting in students’limited understanding of the meaning of traditional songs and the values of nationalism contained in them. This study aims to develop and examine the feasibility, practicality, and effectiveness of aneducational puzzle media based on the song Manuk Dadali to enhance elementary school students’nationalism. This research employed theResearch and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Theresearch subjects consisted of material experts, media experts, language experts, fourth-gradeteachers, and fourth-grade elementary school students. Data were collected through observation, interviews, questionnaires, pretest–posttest assessments, and documentation. Data analysis was conducted using descriptive quantitative and qualitative techniques and N-Gain analysis. The resultsindicate that the educational puzzle media based on the song Manuk Dadali is feasible according to expert validation results, practical based on teacher and student responses, and effective in improvingstudents’ nationalism. This effectiveness is demonstrated by an increase in the average score from38.97 in the pretest to 85.52 in the posttest, with an N-Gain value of 0.76 categorized as high. Therefore, the song